2016
DOI: 10.1038/srep36570
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Ca2+ uptake controls actin cytoskeleton dynamics during cell migration

Abstract: Intracellular Ca2+ signaling regulates cell migration by acting on cytoskeleton architecture, cell directionality and focal adhesions dynamics. In migrating cells, cytosolic Ca2+ pool and Ca2+ pulses are described as key components of these effects. Whereas the role of the mitochondrial calcium homeostasis and the Mitochondria Cacium Uniporter (MCU) in cell migration were recently highlighted in vivo using the zebrafish model, their implication in actin cystokeleton dynamics and cell migration in mammals is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 55 publications
1
71
1
Order By: Relevance
“…and participates in I/R injury through the mechanism of MCU-Ca 2+ overload-mPTP opening. 8,19,20 In the present study, mito- 9 Previous studies have shown that calpain activation can cause cardiac dysfunction and apoptosis through a variety of signalling pathways. 23 In mitochondria, activated calpain cleaves and modifies apoptosis-inducing factor in mitochondria to release it from mitochondria to cytoplasm and initiate apoptosis.…”
Section: Several Studies Have Shown That Mcu Is Over-open During I/rmentioning
confidence: 66%
“…and participates in I/R injury through the mechanism of MCU-Ca 2+ overload-mPTP opening. 8,19,20 In the present study, mito- 9 Previous studies have shown that calpain activation can cause cardiac dysfunction and apoptosis through a variety of signalling pathways. 23 In mitochondria, activated calpain cleaves and modifies apoptosis-inducing factor in mitochondria to release it from mitochondria to cytoplasm and initiate apoptosis.…”
Section: Several Studies Have Shown That Mcu Is Over-open During I/rmentioning
confidence: 66%
“…Of particular note, Ca 2+ signals are necessary to sustain the cell cycle at specific checkpoints such as G 1 /S and G 2 /M transitions [20,21] and mitochondrial Ca 2+ overload is a key event in activating the apoptotic cascade [22]. Cell migration and invasion associated with tumour metastasis are also regulated by Ca 2+ [2326]. …”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria move to the leading edge during migration. In both breast and ovarian cancer cells, mitochondria infiltrate into the leading edge lamellipodia [14,15,20]. To determine whether or not this was the case in non-transformed cells, we used live cell microscopy to image mitochondria in freely migrating NIH3T3 mouse fibroblasts (Fig 1a, Supplementary Video 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports indicate that regulation of calcium flux via the Mitochondrial Calcium Uniporter (MCU) and energy levels via the AMP-activated protein kinase (AMPK) are two pathways through which mitochondria affect migration [14,15]. However, it is unknown what migratory structures in lamellipodia mitochondria might be interacting with.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation